Comparison of the Students’ Perception of Mentimeter and Google Classroom in Teaching Listening - Rizky Mirani Desi Pratama (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2021)
The COVID-19 pandemic has made the government to issue a policy that all teaching and learning activities are carried out through online learning. Changing the face-to-face learning process into an online learning process is a challenge for teachers. Teachers are required to present an interactive online learning process like they usually do in face-to-face learning. This study aims to examine the students’ perception of using media mentimeter and google classroom in learning listening at Bina Sarana Informatika University. This research was conducted using quantitative methods. The sample of this study was third semester students in the listening for specific purposes course . Data collection was done through questionnaire. The results of this study are expected to be a reference for teachers in choosing media in online learning and for improving the quality of the online learning.